Contextual Meaning Of Arab Commentators When Commenting On European Football Broadcasts - Abrar, Atthariqul; Syamsurrijal, Muhammad (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
The aim of this research is to determine the meaning of Arabic interpretive texts using a contextual theory approach. This research relies on library resources, including data collected from the premium Arabic channel Bein Sport, with two well-known commentators, namely Uṣām Asy-Syawālī and Hāfiẓ Ad-Darājī. In this study, researchers found at least forty sentences containing the phrase